2018
DOI: 10.5539/jas.v10n2p335
|View full text |Cite
|
Sign up to set email alerts
|

Viability of Carica papaya L. Seeds by the Tetrazolium Test

Abstract: Germination test for papaya seeds demands thirty days to obtain the results, which is a long period for decision-making. Thus, rapid tests become essential tools to evaluate seed viability, and the tetrazolium test is an alternative for this purpose. Hence, this study aimed to establish the adequate procedure to apply this test, in order to reduce the time of evaluation of papaya seeds. For that, four tetrazolium solution concentrations (0.05, 0.1, 0.5 and 1%) and three staining times (3, 6 and 9 hours) were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Several studies have demonstrated that tetrazolium test is well suited to determine seed viability. For example, the viability of Carica papaya [ 25 ], Nitraria tangutorum , and Nitraria sibirica seed lots [ 27 ] were assessed using the tetrazolium test. Consistent with our findings, these authors demonstrated that a 1% tetrazolium solution worked efficiently and quickly in evaluating the viability and quality of these seed lots prior to germination evaluations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated that tetrazolium test is well suited to determine seed viability. For example, the viability of Carica papaya [ 25 ], Nitraria tangutorum , and Nitraria sibirica seed lots [ 27 ] were assessed using the tetrazolium test. Consistent with our findings, these authors demonstrated that a 1% tetrazolium solution worked efficiently and quickly in evaluating the viability and quality of these seed lots prior to germination evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Viable seeds were stained bright red, while non-viable or dead seeds were unstained or stained white or light red. These evaluations led to three classification of seeds as follows: totally stained, unstained, and partially stained [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Viable seed stained bright red, while pink and very dark red stains are indicative of dead tissue. As such, seeds were classified into three categories based on the following staining patterns: completely stained, completely unstained, and partially stained [55].…”
Section: Tetrazolium Testmentioning
confidence: 99%